The male germ unit association is independently regulated of GUM in Arabidopsis thaliana - Abdur Rauf; Anbang Wang; Yujia Li; Zhihao Lian; Shouxing Wei; Kashmala Jabbar; Muhammad Wisal; Ikramullah Khan; Muhammad Khalid; Jingyang Li (Plant Direct)
Abstract Cytoplasmic projections (CPs) formed by the generative and sperm cells link the male gametes with the vegetative cell (VC) nucleus, which are required to build the male germ unit (MGU) assemblage in the angiosperm pollen grain. As molecular and genetic controls underlying CP development and formation of the MGU are unknown, it was hypothesized that physical association between germ cells and the VC nucleus might be lost in germ unit malformed (gum) mutants or in those which either block generative cell (GC) division or that additionally prevent gamete differentiation. In vivo, analysis of marked cellular components demonstrated a linkage of sperm cells (SCs) and the VC nucleus in gum mutant alleles despite their increased physical separation. Similarly, for several independent classes of bicellular pollen mutants, undivided GCs were associated with the VC nucleus like GCs in wild‐type pollen. We conclude that the early formation of GC CPs to establish the MGU is regulated independently of DUO1‐DAZ1 and DUO3 transcription factors as well as cyclin‐dependent kinase function (CDKA;1). As the absence of cytoplasmic protrusion was expected in the gum mutants in Arabidopsis, early histological studies reported temporal disappearance of cytoplasmic protrusion in several organisms. Our findings demonstrated the striking importance of live imaging to verify the broad conservation of the persistent MGU contact in all the angiosperms and its important role in successful double fertilization.